Effect of different molecular weight polyethylene glycol on flat sheet cellulose acetate membranes for evaluating power density performance in pressure retarded osmosis study. (August 2019) - Sharma, Mukesh; Mondal, Piyal; Chakraborty, Arun; Kuttippurath, Jayanarayanan; Purkait, Mihir
Highlights: Preparation of CA membranes with different molecular weight PEG as additive. Significant enhancement in performance of the membrane was observed in terms of power density. Increase in power density from 0.7 W/m 2 to 3.1 W/m 2 was obtained with CA membranes, modified with PEG 6000. Study provides deeper insights on the performance of membranes to get better power density values. Abstract: In this study, different molecular weights of polyethylene glycol (PEG) (Mw = 4000 and 6000 g/mole) were used as additives for preparations of modified cellulose acetate (CA) flat asymmetric membranes. The effects of additives on membrane characteristics and power density were investigated using the reverse osmosis and pressure retarded osmosis (PRO) methods Membrane characterization and power density of the fabricated membranes were evaluated using the PRO setup. The results show enhancement in the performance of membranes in terms of power density that can be extracted from the membranes with various additives. Furthermore, a comparison was made on the power density obtained using different molecular weights of PEG with CA as a base polymer. A power density of 0.7 W/m 2 was obtained from the unmodified CA membrane, which increased to 2.7 W/m 2 and 3.1 W/m 2 for the modified membranes with PEG 4000 and 6000, respectively. The enhanced power density was due to the better membrane characteristics with respect to its hydrophilicity, pure water flux (PWF), salt rejection and porosity. Therefore, this study provides deeper insights on the performance of membranes with higher molecular weight PEG to get better power density values and attests importance of similar studies in energy science.